Astana's architecture as a representation of the new Kazakhstan : political reading of Astana's built environment - Ivanainen, Zanna (2015)
In my Master’s thesis I explore the political reasons behind Kazakhstan’s Almaty Astana capital relocation and the creation of the new capital Astana with new and futuristic architecture. The strategy is to analyse Kazakhstan’s capital relocation and Astana’s creation and beautification by applying Kenneth Burke’s concepts of the Dramatistic Pentad and the Idea of the Negative. Through Astana’s three most prominent new pieces of architecture, the Baiterek Tower, the Palace of Peace and Reconciliation and Khan Shatyr shopping and entertainment centre, I analyse Kazakhstan’s political aspirations and new representational practises. Through Astana’s architecture and Burke’s Dramatistic Pentad and the Idea of the Negative I enquire political messages and symbols in Astana’s new architecture and built environment. Additionally, to get a more comprehensive picture on Kazakhstan’s politics and aspirations, I employ Kazakhstan’s government’s publications on the new capital, speeches and works of Kazakhstan’s president Nursultan Nazarbayev, and western and Kazakh newspaper articles on Kazakhstani capital relocation and Astana’s mental and physical creation. In my thesis I argue that Kazakhstan’s capital relocation and the Astana project are political acts; they are meant to impress national and international audiences, attract foreign investment, to put Astana and Kazakhstan on the map, and to add Astana and Kazakhstan’s prestige in the world. Kazakhstan’s authoritarian president Nazarbayev has been promoting Astana and Kazakhstan’s mental image around the world; he has been advertising Kazakhstan as a modern and developed country, and he has been utilizing Astana’s development and new architecture to do so. In my thesis I asked, what are the political messages in Astana’s new architecture, and what does Astana’s urban symbolism and architecture reveal about the aspirations and desires of Kazakhstan and Kazakhstan’s authoritarian president Nazarbayev. I found that Astana’s new architecture, particularly on the Left Bank of the Ishim River that splits the city in half, is part of president Nazarbayev’s state- and nation building efforts; it enacts Nazarbayev’s vision of Kazakhstan’s post Soviet modernity and establishes the state as the agent of modernity and constructor of the Kazakh nation-state. However, much of the change in Astana and Kazakhstan has been very superficial, and the hypermodern image of the Left Bank, propagated nationally and internationally, does not match the rest of the capital or the country.